2005
DOI: 10.1007/s10450-005-5397-6
|View full text |Cite
|
Sign up to set email alerts
|

Expressiveness of Adsorption Measurements for Characterization of Zeolitic Materials—A Review

Abstract: This critical review concerns the author's results and experience in adsorption studies on molecular sieves comprising crystalline microporous aluminosilicates and aluminophosphates as well as amorphous mesoporous aluminosilicates. The discussion is mainly based on three distinctly different standard adsorbates: nitrogen, benzene, and water. The highlights or advantages and the shortcomings or limitations are considered from the points of view of the experimental procedures and expressiveness or concluding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…These cations can move freely along the diffusion paths formed by voids and channels in the zeolite structure, and are responsible for the ion conducting properties of zeolites [22]. Zeolites are highly hydrophilic solids and have a high water sorption capacity because of the charged anionic framework and the extra-framework cations [23,24] in addition to their open structure, high pore volume and surface area.…”
Section: Introductionmentioning
confidence: 99%
“…These cations can move freely along the diffusion paths formed by voids and channels in the zeolite structure, and are responsible for the ion conducting properties of zeolites [22]. Zeolites are highly hydrophilic solids and have a high water sorption capacity because of the charged anionic framework and the extra-framework cations [23,24] in addition to their open structure, high pore volume and surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Role of Water on EtO Removal. H 2 O adsorption in acidified ZSM-5 has been extensively investigated both experiment-ally , , and computationally , due to its importance in a wide range of acid-catalyzed reactions. Water adsorbs strongly onto Brønsted acid centers associated with H−ZSM-5, leading to a linear relationship between the amount of adsorbed water and the aluminum content of the zeolite. ,,, For example, Sano et al reported water adsorption isotherms at 25 °C for H−ZSM-5 crystals with SiO 2 /Al 2 O 3 ratios between 71 and 3300.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O adsorption in acidified ZSM-5 has been extensively investigated both experiment-ally , , and computationally , due to its importance in a wide range of acid-catalyzed reactions. Water adsorbs strongly onto Brønsted acid centers associated with H−ZSM-5, leading to a linear relationship between the amount of adsorbed water and the aluminum content of the zeolite. ,,, For example, Sano et al reported water adsorption isotherms at 25 °C for H−ZSM-5 crystals with SiO 2 /Al 2 O 3 ratios between 71 and 3300. The authors noted (1) a linear increase in the amount of adsorbed water with increased partial pressure and (2) the strong dependency on the amount of adsorbed water and the SiO 2 /Al 2 O 3 ratio.…”
Section: Resultsmentioning
confidence: 99%
“…For crystalline zeolites as micro- porous sorbents, sorption isotherms of type I are typically expected (Barrer 1978;Kornatowski 2005). Such isotherms are characterized under very low P /P 0 by very high Vs, corresponding to sorbate molecule binding in micropores, and further by Vs "saturation" (plateau area of an isotherm) (Gregg and Sing 1982;Aranovich and Donohue 1998).…”
Section: Sorption Isothermsmentioning
confidence: 98%